Red Ginseng Supplementation More Effectively Alleviates Psychological than Physical Fatigue - Choi, Ji Young (The Korean Society of Ginseng, 2011)
Red ginseng (RG, the extract of Panax ginseng Meyer) has various biological and psychological activities and may also alleviate fatigue-related disorders. The present study was undertaken to evaluate what kind of fatigue red ginseng alleviate. Animals were orally administered with 50, 100, 200, 400 mg/kg of RG for 7 days. Before experiments were performed. Physiological stress (swimming, rotarod, and wire test) are behavioral parameters used to represent physical fatigue. Restraint stress and electric field test to a certain degree, induce psychological fatigue in animals. Plasma concentration of lactate and corticosterone (CORT) were also measured after these behavioral assays. RG supplementation (100 mg/kg) increased movement duration and rearing frequency of restrainted mice in comparison with control. 100 and 200 mg/kg of RG increased swimming time in cold water (8±4℃) while at 100 mg/kg, RG increased electric field crossing over frequencies. 50, 100 and 200 mg/kg RG prolonged running time on the rotarod and at 100 mg/kg, it increased balancing time on the wire. RG at those doses also reduced falling frequencies. RG supplementation decreased plasma CORT levels, which was increased by stress. Lactate levels were not significantly altered. These results suggest that RG supplementation can alleviate more the damages induced by psychological than physical fatigue.